2005
DOI: 10.1002/jnr.20550
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide regulation of the tumor suppressor phosphatase PTEN in rafts isolated from neurotumor cell lines

Abstract: The neutral sphingolipid ceramide has been implicated in the apoptotic death of cells by a number of different mechanisms, including activation of protein kinase B (Akt) phosphatase. Here we present evidence that ceramide recruits the tumor suppressor PTEN (phosphatase and tensin homolog deleted from chromosome 10) into membrane microdomains (rafts), where it could act to reduce the levels of polyphosphoinositides necessary for the activation of Akt. A PTEN construct with a red-fluorescent protein (RFP) tag wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 52 publications
6
47
0
Order By: Relevance
“…In addition to promoting the recruitment of PKB and aPKC1/z, ceramide exposure can also significantly elevate levels of phosphatase and tensin homologue deleted on chromosome ten (PTEN) in caveolin-enriched DRM fractions [53,60]. The tumour suppressor PTEN acts as a phosphoinositide phosphatase and its increased abundance in CEMs would likely result in reduced localised levels of 3′-phosphoinositides.…”
Section: Influence Of Caveolae In Mediating the Effects Of Ceramidementioning
confidence: 99%
“…In addition to promoting the recruitment of PKB and aPKC1/z, ceramide exposure can also significantly elevate levels of phosphatase and tensin homologue deleted on chromosome ten (PTEN) in caveolin-enriched DRM fractions [53,60]. The tumour suppressor PTEN acts as a phosphoinositide phosphatase and its increased abundance in CEMs would likely result in reduced localised levels of 3′-phosphoinositides.…”
Section: Influence Of Caveolae In Mediating the Effects Of Ceramidementioning
confidence: 99%
“…This idea is supported by the finding that the A. actinomycetemcomitans CdtB subunit exhibits phophatidylinositol-3,4,5-triphosphate (PIP3) phosphatase activity similar to that of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) (30,52). A previous study found that PTEN normally has a generalized cytosolic and membrane distribution but is recruited into membrane rafts when cells are treated with ceramide (18). We found that both CdtA and CdtC interact with lipid rafts (predominantly localized in cholesterol-rich microdomains) to enhance the association of CdtB with the cell membrane and its subsequent delivery into the cells.…”
Section: Discussionmentioning
confidence: 90%
“…Ceramide is indeed able, by directly promoting the recruitment into lipid raft of phosphatase and tensin homologue (43) and/or by indirectly activating ceramide-activated protein phosphatase 2A (43,44), to inhibit specifically this pathway, conducting to NF-κB inactivation and to decreased Bcl-xL expression. Conversely, both SphK1 and, indirectly, S1P by acting in an autocrine loop via its S1PR/Edg receptors are able to stimulate this same pathway (45,46).…”
Section: Discussionmentioning
confidence: 99%